Role and Mechanism of Freeze-Dried Powder of Phyllanthus emblica L. in Antagonizing Liver Injury Induced by Subacute Cadmium Exposure in Mice - ZHAO Bo, GU Shiyan, MEI Zongqin, LI Wenhong, MA Shunrong, SHEN Kaiyan, HE Zuoshun (Shipin Kexue)
Objective: To investigate the effect of freeze-dried powder of Phyllanthus emblica L. (PEFP) on cadmium chloride (CdCl2)-induced subacute liver injury in mice and to analyze the underlying mechanism by transcriptomics. Methods: Male KM mice were randomly divided into four groups with 6 animals per group: control, PEFP (300 mg/kg), CdCl2 (3 mg/kg) and PEFP + CdCl2 (300 mg/kg PEFP + 3 mg/kg CdCl2). PEFP was gavaged once a day to mice, and CdCl2 was intraperitoneally injected into mice every other day. The administration period lasted for 28 days. After euthanasia, liver tissues were collected for the determination of cadmium content, superoxide dismutase (SOD), and glutathione peroxidase (Gpx) activities, and serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) activities were measured. Additionally, hepatic cell morphology was observed by hematoxylin-eosin (HE) staining, the apoptosis rate was determined by the terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) assay, differentially expressed genes were determined by RNA sequencing, and protein expression levels encoded of the selected differentially expressed genes were detected by Western blot (WB). Results: Compared with the control group, body mass gain rate significantly decreased in the CdCl2 exposure group ((13.97 ± 2.06)%) (P < 0.05), liver cadmium accumulation ((3.49 ± 0.09) μg/kg), and serum AST, ALT and ALP levels ((707.55 ± 60.19), (614.58 ± 24.40), and (186.85 ± 12.51) U/L, respectively) and hepatocyte apoptosis rate ((32.89 ± 2.53)%) increased (P < 0.05). However, CdCl2 combined with PEFP treatment could significantly reverse the above changes caused by cadmium (P < 0.05). RNA sequencing showed that 69 genes were differentially expressed after PEFP intervention (14 up-regulated and 55 down-regulated), the encoded protein of which were associated with inflammation, oxidative damage and apoptosis. We selected four proteins (AnnexinA2, S100A11, Mcp1, and galectin3) encoded of these differentially expressed genes for further verification by WB analysis, and the results were consistent with those of RNA sequencing, suggesting that these proteins were involved in PEFP antagonization of cadmium-induced effects. Conclusion: PEFP exhibited an antagonistic effect against cadmium-induced subacute liver injury in mice. This protective mechanism may be attributed to its capability to alleviate hepatic tissue damage by inhibiting inflammatory responses, oxidative stress, and apoptosis.